Evaluasi kandungan gula susu UHT anak di Indonesia: Kesesuaian label gizi dengan klaim ‘pilihan lebih sehat’ - Fajri, Aulia Irhamni; Suhaima, Nurafi Razna (UHAMKA PRESS, 2025)
Indonesia has implemented the front-of-pack “Healthier Choice” label to guide consumers particularly parents in selecting products with lower sugar content. However, the use of this label remains voluntary, resulting in inconsistent application across children’s UHT milk products. This study analyzes the sugar content and ingredient composition of 21 small-pack (100–125 mL) UHT milk products marketed for children and collected from five major brands: Frisian Flag, Dancow, Indomilk, Ultra Milk, and Greenfields. Findings indicate that 19 out of 21 products comply with the maximum sucrose limit established by Indonesia’s BPOM Regulation No. 26/2021 (≤6 g per 100 mL for monosaccharides and disaccharides excluding lactose). Despite this compliance, there is substantial variability in ingredient composition, including differing proportions of fresh milk, the use of recombined milk, and the presence of food additives such as synthetic colorants and flavorings. Several products displayed the “Healthier Choice” label even though they contained synthetic dyes such as ponceau 4R and tartrazine, which warrant careful monitoring in foods intended for children. Nutrient-related claims such as “contains vitamins,” “omega 3 and 6,” and “source of calcium” were often promotional in nature and lacked sufficient quantitative justification. These findings underscore the need for greater transparency in labeling and stronger regulation of ingredient composition to ensure adequate consumer protection. The study recommends harmonizing national regulations with WHO, FDA, and ASEAN policies to improve the accuracy of nutrition information and enhance the effectiveness of front-of-pack labeling systems.